2019
DOI: 10.1016/j.devcel.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome-Rich Enterocytes Mediate Protein Absorption in the Vertebrate Gut

Abstract: Highlights d Lysosome-rich enterocytes (LREs) internalize and digest dietary protein intracellularly d LREs are conserved between zebrafish and mammals d Cubn, Amn, and Dab2 mediate high-capacity protein uptake in LREs d Loss of LRE function impairs growth and survival in zebrafish and mice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
145
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(160 citation statements)
references
References 86 publications
(113 reference statements)
14
145
0
1
Order By: Relevance
“…In contrast, in the distal small intestine (ileum), the fetaltype epithelium internalizes luminal material via the apical endocytic complex and forms large digestive vacuoles that make up most of the cytoplasmic content (26,52), allowing little macromolecules to pass the epithelium intact. The endocytosis machinery in mouse ileal enterocytes was recently identified and described as consisting of the multi-ligand scavenger (protein) receptors, Cubulin and Amnionless, together with the adaptor protein, Dab2, as mediators of the endocytosis mechanism (53,54). In fact, these highly endocytic intestinal cells equipped with this multi-ligand endocytic machinery were also found in the zebrafish, indicating a conserved presence and function in vertebrates.…”
Section: Lagomorph and Rodent Speciesmentioning
confidence: 99%
“…In contrast, in the distal small intestine (ileum), the fetaltype epithelium internalizes luminal material via the apical endocytic complex and forms large digestive vacuoles that make up most of the cytoplasmic content (26,52), allowing little macromolecules to pass the epithelium intact. The endocytosis machinery in mouse ileal enterocytes was recently identified and described as consisting of the multi-ligand scavenger (protein) receptors, Cubulin and Amnionless, together with the adaptor protein, Dab2, as mediators of the endocytosis mechanism (53,54). In fact, these highly endocytic intestinal cells equipped with this multi-ligand endocytic machinery were also found in the zebrafish, indicating a conserved presence and function in vertebrates.…”
Section: Lagomorph and Rodent Speciesmentioning
confidence: 99%
“…These findings are supported by numerous studies that have used D-xylose, a small sugar that is readily absorbed via transcellular transport, to measure transcellular uptake in malabsorption conditions (Antunes et al, 2009;Craig and Atkinson, 1988;Hope et al, 2012). In addition, dysfunction of protein complexes involved in internal cell transport mechanisms have long been implicated in malabsorption conditions in humans (Park et al, 2019;Tonucci et al, 2018Tonucci et al, , 2017.…”
Section: Loss-of-function Intestinal Phenotypementioning
confidence: 71%
“…The most frequently described mechanism of transcellular intake is pinocytosis, which is a fluidphase endocytosis in which a molecule transits across the cell through invaginations of the apical membrane that form vesicles containing digestive enzymes (Kiss and Botos, 2009;Snoeck et al, 2005). In a recent study, Park et al (2019), characterized a subclass of specialized enterocytes, referred to as lysosome-rich enterocytes (LREs), found to be morphologically and functionally conserved between zebrafish and mouse. These authors showed that LREs function essentially in the uptake of proteins by fluid-phase endocytosis and by receptor-mediated endocytosis modulated by a complex of transmembrane receptors comprising Cubilin (Cubn) and Amnionless (Amn), and the endocytic adaptor Dab2.…”
Section: Absorption Of Nutrientsmentioning
confidence: 99%
See 2 more Smart Citations